Misuse and Modification of Fireworks With Fatal Injury. (June 2015) - Fulcher, James; Luttrell, Harrison; Harvey, Whit; Ward, Michael
Abstract : Abstract: Fireworks deaths are a rare event in the United States with minor injuries comprising most adverse events. We report the case of misuse and modification of a large "mortar" firework with fatal results. In this case, the firework charge was modified with additional fuses and placed into the launcher upside down. The decedent then held the mortar base closely to his chest and lit the modified fuse. The resulting explosion caused severe blunt force trauma with significant hydrostatic shock damage to the heart and liver. This cause highlights the dangers of fireworks, particularly when misused.